DETERMINAN KECURANGAN AKUNTANSI PADA PEMERINTAH DAERAH DI INDONESIA: SYSTEMATIC LITERATURE REVIEW - Mardiyanto, Mardiyanto (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
Accounting fraud in the Government sector identical to corruption behavior is indicated that there are still many occurring at various levels of government in Indonesia, both at the central and regional levels. This study aims to find out the main factors that influence the occurrence of accounting fraud that can be considered in the area of policy formulation to prevent accounting fraud. Research conducted in previous studies using systematic literature review (SLR) research methods that take local government as a research object. The selection of journal articles published during 2018 to 2022 on Garuda journal database on the https://garuda.kemdikbud.go.id/ website using the Preferred Reporting Items for Systematic Review (PRISMA) method was obtained by 22 articles that met the requirements for analysis. The main results of this study found that the most influential factors (determinants) against the occurrence of accounting fraud were Internal Control Systems, information asymmetry, compliance with accounting standars, compensation suitability, individual morality and unethical behavior